NOTION AND TYPES OF EXTRAHAZARDOUS OBJECTS IN CRIMINAL LAW - I. I. Bikeyev (Russian Journal of Economics and Law, 2007)
The article, from the viewpoint of criminal law science, presents the author's definition of extrahazardous objects, their signs and classification. The author views the correlation of these objects with the sources of danger and other related objects. Justification is given to the criminalization of the publicly dangerous form of handling such objects.